If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x-4)/3=2(x+1)/6
We move all terms to the left:
6(x-4)/3-(2(x+1)/6)=0
We calculate fractions
6x/()+(-(2(x+1)*3)/()=0
We calculate terms in parentheses: +(-(2(x+1)*3)/(), so:We get rid of parentheses
-(2(x+1)*3)/(
We multiply all the terms by the denominator
-(2(x+1)*3)
We calculate terms in parentheses: -(2(x+1)*3), so:We get rid of parentheses
2(x+1)*3
We multiply parentheses
6x+6
Back to the equation:
-(6x+6)
-6x-6
Back to the equation:
+(-6x-6)
6x/()-6x-6=0
We multiply all the terms by the denominator
6x-6x*()-6*()=0
We add all the numbers together, and all the variables
6x-6x*()=0
| 7.34+7.45-11.2z+11.2z=-3.7-15.5z | | 8(y+40-2(y-1)=70-3y | | -3−4f=-7f | | -1−3d=-4d | | 120h+5h=h | | 3x-40=38 | | 0.3(y-2)=0.4y | | 9j=5+10j | | 10+x-25=13+5x | | (3x-14)(2x+10)=180 | | 15x-6=14x | | r^2–50=50 | | 3x+5+4x=-8+5x+3 | | x+2x-12=90 | | 4n=16+2n | | s-21-19=121 | | 4(d-2)=8d-4 | | 32=−4−9n | | 64=-9a+a | | 6y+37=166 | | (7x)(10x+5)=90 | | -16q-12+3q=-12q+3 | | 4x+8=2x+2x= | | 6y+137=166 | | 17+25=t-33 | | 2(4x+7)=3x-11 | | (7x)(10x+5)=180 | | 7x+12=-3x+62 | | 0.08x+0.05(11000-x)=760 | | 20+3b=13-17b | | 20+3=13-7b | | -4/3x-11=13 |